Moving Cupping and Wet Cupping Based on Bibliometric Analysis and Review: The Novelty of Combination Cupping - Dian Wahyuni (STIKep PPNI Jawa Barat, 2022)
Aims: Describe the significance of the bibliography in assisting cupping research. Methods: This research is a descriptive analytic study. using the Publish or Perish software, the title is about cupping, the period 0–2022 and then analyzed using VOSviewer, after that reviewing articles about moving cupping and wet cupping for the period 2019–2022. Results:Found 1057 articles about cupping indexed by Scopus. There were four large clusters in the journal network. Wet cupping tended to be new in publication but wet cupping did not appear in overlays. Wet cupping had relatively many publications compared to moving cupping. The differences in procedures, even though the intervention was the same in cases with wet cupping therapy and cases with moving cupping therapy, were striking. Conclusion: According to VOS observers, even though scientific papers about cupping have been researched since 1826 and indexed by Scopus, wet cupping is still popular and the combination of moving and wet cupping is still hardly ever explored. Recommendation: The bibliography can be used as a reference for the collection of research results and as a reference for other researchers to determine the variables of cupping research.